Student’s environmental literacy: An educational program reflections for sustainable environment - I Made Surya Hermawan; Hadi Suwono; Anak Agung Inten Paraniti; Jittawisut Wimuttipanya (University of Muhammadiyah Malang, 2022)
This study aims to reflect on educational programs on environmental sustainability by measuring the environmental literacy of high school students in Denpasar City and identifying the relationship between environmental literacy domains. The research subjects were 154 students who were taken by random sampling technique. Data analysis used descriptive statistics, Pearson product-moment correlation test, and multiple regression test. The results of data analysis showed: 1) environmental literacy of high school students in Denpasar City was categorized as moderate; 2) the domain of knowledge and cognitive skills is high, while the domain of attitudes and behavior towards the environment is moderate; 3) the knowledge domain has a significant relationship with the cognitive skill, the attitude has a significant relationship with the behavioral domain, while there is no significant relationship between the knowledge domain and the attitude domain. The findings of this study indicate that the empowerment of environmental literacy through educational institutions is not yet optimal. Therefore, local and operational educational policies are needed in the learning process to improve the environmental literacy of high school students in Denpasar City